Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1159/000093488
|View full text |Cite
|
Sign up to set email alerts
|

Use of Complementary Medicine in Switzerland

Abstract: Within the framework of the Swiss governmental Program of Evaluation of Complementary Medicine (PEK) we assessed the prevalence, use, perceived effectiveness and appreciation of complementary medicine (CAM) in Switzerland, according to published surveys. Materials and Methods: Search was performed through electronic databases, by hand-searching and by contacting experts at universities, hospitals, health insurances, patient organizations and pharmaceutical companies. Results: Surveys were carried out among the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
37
0
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 3 publications
1
37
0
6
Order By: Relevance
“…11 CAM is often used in Switzerland. [12][13][14][15] A survey published in 2002 described that 30% of the Swiss people did use some form of CAM: 12% had used homeopathy, 11% had used Traditional Chinese Medicine (TCM) or acupuncture, 5% herbal medicine (phytotherapy), 2% anthroposophic medicine, and 1% neuraltherapy. 16 The use of CAM in Switzerland, its efficacy, appropriateness, and cost-effectiveness have been evaluated within the frames of a federal program (Complementary Medicine Evaluation Program, PEK), which revealed that CAM was associated with a higher patient satisfaction, weaker=less frequent side-effects, and lower costs than conventional medicine (CM).…”
Section: Introductionmentioning
confidence: 99%
“…11 CAM is often used in Switzerland. [12][13][14][15] A survey published in 2002 described that 30% of the Swiss people did use some form of CAM: 12% had used homeopathy, 11% had used Traditional Chinese Medicine (TCM) or acupuncture, 5% herbal medicine (phytotherapy), 2% anthroposophic medicine, and 1% neuraltherapy. 16 The use of CAM in Switzerland, its efficacy, appropriateness, and cost-effectiveness have been evaluated within the frames of a federal program (Complementary Medicine Evaluation Program, PEK), which revealed that CAM was associated with a higher patient satisfaction, weaker=less frequent side-effects, and lower costs than conventional medicine (CM).…”
Section: Introductionmentioning
confidence: 99%
“…1 The use of CAM in Switzerland and its effectiveness, appropriateness, and efficiency were addressed in 2005 by the government Program of Evaluation of Complementary Medicine, [2][3][4] which showed that approximately half of the population uses CAM. The popularity of this type of medicine was corroborated by a people's vote in 2009 in which about two thirds of the citizens favored the possibility of using CAM.…”
mentioning
confidence: 99%
“…D'après l'enquête suisse sur la santé 2007, 31 % de la population du canton de Vaud y a fait appel au moins une fois au cours de l'année précédant l'analyse [2] . Wolf et al [3] ont mis en évidence une prévalence d'utilisation en Suisse de 49 ± 22 %. Ces médecines sont largement recherchées par les patients en complément à la médecine conventionnelle, bien que 77 % d'entre eux ne disent pas à leur médecin généraliste qu'ils y recourent [4] .…”
Section: Results Of a Swiss Surveyunclassified